Castleman’s disease – a case report - Maciej Wilczak; Małgorzata Kampioni; Jacek Szmeja (Videosurgery and Other Miniinvasive Techniques)
Angiofollicular lymphoid hyperplasia (Castleman’s disease) is a very rare disease of lymphatic tissue, manifested by overgrowth of B lymphocytes and plasma cells in lymph nodes. The aetiology of this lymphocyte hyperplasia has not been conclusively explained and its pathogenesis is still not known. There are three types of the disease based on histological criteria: plasma-cell, hyaline-vascular and transitional. Clinically it is classified into two forms, localized and multicentric (disseminated/generalized). Castleman’s disease may develop not only in lymph nodes, but also in other organs and tissues, e.g. larynx, pancreas, meninges, etc. In patients with localized Castleman’s disease the most important therapy is radical surgery of the tumour, which creates conditions leading to complete recovery. In the case of multicentric diagnosis the prognosis is unsure.The paper describes an atypical case of Castleman’s disease, diagnosed as localized form in the patient’s pelvis minor with accompanying cystic changes in the mesocolon.